In vivo physiological recording from the lateral line of juvenile zebrafish. (9th June 2016) - Olt, Jennifer; Allen, Claire E.; Marcotti, Walter
Abstract : Key points: Zebrafish provide a unique opportunity to investigate in vivo sensory transduction in mature hair cells. We have developed a method for studying the biophysical properties of mature hair cells from the lateral line of juvenile zebrafish. The method involves application of the anaesthetic benzocaine and intubation to maintain ventilation and oxygenation through the gills. The same approach could be used for in vivo functional studies in other sensory and non‐sensory systems from juvenile and adult zebrafish. Abstract: Hair cells are sensory receptors responsible for transducing auditory and vestibular information into electrical signals, which are then transmitted with remarkable precision to afferent neurons. The zebrafish lateral line is emerging as an excellent in vivo model for genetic and physiological analysis of hair cells and neurons. However, research has been limited to larval stages because zebrafish become protected from the time of independent feeding under European law (from 5.2 days post‐fertilization (dpf) at 28.5°C). In larval zebrafish, the functional properties of most of hair cells, as well as those of other excitable cells, are still immature. We have developed an experimental protocol to record electrophysiological properties from hair cells of the lateral line in juvenile zebrafish. We found that the anaesthetic benzocaine at 50 mg l −1 was an effective and safe anaesthetic to use on juvenile zebrafish. Concentrations up to 300 mg l −1 did not affect the electrical properties or synaptic vesicle release of juvenile hair cells, unlike the commonly used anaesthetic MS‐222, which reduces the size of basolateral membrane K + currents. Additionally, we implemented a method to maintain gill movement, and as such respiration and blood oxygenation, via the intubation of > 21 dpf zebrafish. The combination of benzocaine and intubation provides an experimental platform to investigate the physiology of mature hair cells from live zebrafish. More generally, this method would allow functional studies involving live imaging and electrophysiology from juvenile and adult zebrafish. Key points: Zebrafish provide a unique opportunity to investigate in vivo sensory transduction in mature hair cells. We have developed a method for studying the biophysical properties of mature hair cells from the lateral line of juvenile zebrafish. The method involves application of the anaesthetic benzocaine and intubation to maintain ventilation and oxygenation through the gills. The same approach could be used for in vivo functional studies in other sensory and non‐sensory systems from juvenile and adult zebrafish.